Періодичні розв'язки імпульсних еволюційних систем з необмеженими не лінійностями - Роговченко, Ю.В. (Український математичний журнал, 1993)
The conditions are established, under which periodic solutions of pulse evolutionary systems with unbounded (inx) operators on the right-hand sides exist and are stable.